(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2019)
Leukocoria is defined as a white reflex in the pupillary area. It can reveal several intraocular pathologies. The aim of our study is to draw the epidemiological and clinical profile of the leukocoria at the Joseph Ravoahangy Andrianavalona University Hospital (CHUJRA) in Antananarivo Madagascar and to discuss the different causes. This is a retrospective study for two and a half years including patients aged between 0 and 10 years at the Ophthalmology service of the CHU-JRA. Leukocoria was found in 40 eyes of 27 patients with a mean age of 4 years. It was unilateral in 51.84% of case. The etiologies were congenital cataract in 48.14%, retinoblastoma in 33.33% and post traumatic cataract in 18.51% of case. Leukocoria is an indicative of serious eye disease which can threaten the vision and the life prognosis in some cases. There are many etiologies made by the literature. All leukocoria should be explored to establish the diagnosis of all possible etiologies in order to ensure an adequate care for each case.